Konsep Diri, Lansia KONSEP DIRI PADA LANSIA DI PANTI WERDHA PANGESTI LAWANG - Santi S (Jurnal Keperawatan Malang, 2018)
Abstract Self concept will grow with the increasing of age. Self concept in the elderly is more influenced byphysical problems, psychosocial, spiritual and economic. Most of them being carry to nursing home bytheir families with a reason that they are not able to take care of their elderly at home. It its concequences a lot of elderly think negatively about the decision to put them at nursing home. Negative thinking makes them to have a negative self –concept. Purpose of this study is to know the self-concept of elderly in Nursing home Pangesti Lawang. This study used discriptive method with purposive sampling (46 respondents) and using questionnaires to collecting data. It is the negativeresult were 1) Self image (63%), 2) Self Ideal (52,2%), 3) Self identity (58,7%), 6) Self-concept ofelderly who lives in the nursing home (63%). While the negative result showed: 1) Self esteem(56,5%), 2) Role performance (69,6%). Recommendation of this study to involve elderly in activities that they can do, can be prayer together, gymnastics, eat together, cleaning up, singing together andappreciation to the elderly is an important issue Keywords: self-concept, self-image, self ideal, self-esteem, role performance, self identity, elderly